KEBAN BARAJ GÖLÜNDEN YAKALANAN BALIKLARDA GÖRÜLEN EKSTERNAL PARAZİTLERİN İNCELENMESİ - SAĞLAM, NAİM (Fırat Üniveristesi, 1992)
[Abstract Not Available]
Investigation of external parasites on fish cought in lake Keban
Keywords: Su Ürünleri; Aquatic Products